(untitled) (Fiep Bulletin - online, 2014)
The physical activity acquired in the last few decades, a degree of extreme importance as for the health human being. The current research in this area shows clearly that good part of the occurrence of illnesses is also caused by the physical inactivity. However, the human being is each more conscientious time on the cares necessary to get one better quality of life, and that this includes the movement corporal, that is, this conscience is changing behaviors and styles of life. In this direction, the aeróbica gymnastics and the located one had conquered an important space today, being comprovadamente activities that assist in the prevention and diverse recovery of males related to the health human being. The research had for objective to analyze the importance of the aeróbica and located gymnastics in the improvement of the flexibility of women of 20 the 40 years. The collection of data if gave through the evaluation of flexibility, being analyzed the segments knees and shoulders. 26 women, being divided in two groups with 13 participants each had been analyzed, being Active a called group (practically of physical activity) and another Sedentary one (not practicing). This was used to verify the existing differences between the groups. The analysis statistics of the data was through Test T of Student. The results gotten with the Sedentary group suggest that it did not have significant modifications in the analyzed questions, whereas the Active group presented 99% of effectiveness as for the improvement of the flexibility of the analyzed variants, in the case flexão and extension of shoulders and flexão of knees. This strengthens the idea of that the work of aeróbica and located gymnastics assists in the development of flexibility, improving the capacity to articulate, as well as preventing possible injuries.